A Multistage Model of Bargaining - Sobel, Joel; Takahashi, Ichiro (Review of Economic Studies, 1983)
This paper presents a simple, multistage model of bargaining wherein a seller makes an offer that can be either accepted or refused.If rejected, the process continues.How the seller's ability to make commitments affects bargaining outcomes is analysed by comparing the commitment equilibria to those arising when commitment is impossible.The effects of increasing uncertainty about preferences and varying the length of the bargaining horizon are analysed.The ways in which the bargaining environment can be changed to improve outcomes are discussed.